The Substantial Model Of The Photon - Fedosin Sergey, G. (University of Eloued جامعة الوادي, 2017)
It is shown that the angular frequency of the photon is nothing else than the averaged angular frequency of revolution of the electron cloud’s center during emission and quantum transition between two energy levels in an atom. On assumption that the photon consists of charged particles of the vacuum field (of praons), the substantial model of a photon is constructed. Praons move inside the photon in the same way as they must move in the electromagnetic field of the emitting electron, while internal periodic wave structure is formed inside the photon. The properties of praons, including their mass, charge and speed, are derived in the framework of the theory of infinite nesting of matter. At the same time, praons are part of nucleons and leptons just as nucleons are the basis of neutron stars and the matter of ordinary stars and planets. With the help of the Lorentz transformations, which correlate the laboratory reference frame and the reference frame, co-moving with the praons inside the photon, transformation of the electromagnetic field components is performed. This allows us to calculate the longitudinal magnetic field and magnetic dipole moment of the photon, and to understand the relation between the transverse components of the electric and magnetic fields, connected by a coefficient in the form of the speed of light. The total rest mass of the particles making up the photon is found, it turns out to be inversely proportional to the nuclear charge number of the hydrogen-like atom, which emits the photon.
Article in Journal of Fundamental and Applied Sciences Vol 09, N 01
Keywords: matter waves; quantum gravity; electromagnetic interaction; magnetic moments; properties of photon.